Thrombo-occlusive left lateral medullary syndrome (Wallenberg syndrome) with iron deficiency anemia: A case report with clinical insights (Indian Journal of Case Reports, 2026)
Left lateral medullary syndrome (Wallenberg syndrome) is a rare ischemic stroke caused by infarction in the lateral medulla, typically presenting with vertigo, ataxia, and sensory deficits. This case reports a rare presentation of Wallenberg syndrome in a 48-year-old female with coexisting severe iron deficiency anemia (IDA). The patient presented with acute dizziness, vomiting, left-sided ptosis, and contralateral limb weakness. Magnetic resonance confirmed infarcts in the left lateral medulla and cerebellum, as well as the anterior capsulo-ganglionic region, explaining the atypical presentation of limb weakness. Angiography revealed complete thrombo-occlusion of the left vertebral artery. Laboratory evaluation identified significant IDA as a potential exacerbating risk factor. The patient was managed with antiplatelets, statins, and intravenous iron replacement, resulting in significant neurological recovery. This case underscores the importance of evaluating IDA as a potential contributing factor in ischemic stroke, particularly in women without traditional vascular risk factors.